2014
DOI: 10.1038/cddis.2014.158
|View full text |Cite
|
Sign up to set email alerts
|

A gain-of-function mutant p53–HSF1 feed forward circuit governs adaptation of cancer cells to proteotoxic stress

Abstract: To overcome proteotoxic stress inherent to malignant transformation, cancer cells induce a range of adaptive mechanisms, with the master transcription factor heat-shock factor 1 (HSF1)-orchestrated response taking center stage. Here we define a novel gain-of-function of mutant p53 (mutp53), whereby mutp53-overexpressing cancer cells acquire superior tolerance to proteotoxic stress. mutp53 via constitutive stimulation of EGFR and ErbB2 signaling hyperactivates the MAPK and PI3K cascades, which induce stabilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 37 publications
5
101
1
Order By: Relevance
“…Consistent with our current in vivo data, we recently showed in vitro that RNAi mediated downregulation of mutp53 in ErbB2 positive SKBR3 human breast cancer cells promotes ErbB2 degradation 32 . Conversely, ectopic overexpression of the R175H p53 mutant increases ErbB2 levels in SKBR3 cells 32 .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with our current in vivo data, we recently showed in vitro that RNAi mediated downregulation of mutp53 in ErbB2 positive SKBR3 human breast cancer cells promotes ErbB2 degradation 32 . Conversely, ectopic overexpression of the R175H p53 mutant increases ErbB2 levels in SKBR3 cells 32 .…”
Section: Resultssupporting
confidence: 91%
“…Consistent with our current in vivo data, we recently showed in vitro that RNAi mediated downregulation of mutp53 in ErbB2 positive SKBR3 human breast cancer cells promotes ErbB2 degradation 32 . Conversely, ectopic overexpression of the R175H p53 mutant increases ErbB2 levels in SKBR3 cells 32 . Hence, mutp53, via amplification of ErbB2 signaling, may promote the expansion of the SC pool, leading to increased metastatic recurrence, as observed in mutp53/HER2 -positive breast cancer patients 5 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It has been reported that mut p53 positively regulates HSF1 levels and activity [23]. We also confirmed that the level of HSF1 was decreased in amurensin G-treated MCF7-MDR cells transfected with control siRNA but not CHIP knock-downed cells.…”
Section: Chip-mediated Mut P53 Degradation Leads To Downregulation Ofsupporting
confidence: 76%
“…Similar findings with respect to stabilization of Hsp90 client proteins by Her2/HSF1 axis came from a study where inhibition of Her2 signaling resulted in the inhibition of HSF1 activity (phosphorylation) and the destabilization of HSP90 clients including MIF (macrophage migration inhibitory factor) and AKT (17). Recent studies have demonstrated that overexpression of mutant p53 also activates EGFR/Her2, leading to enhanced PI3K and MAPK signaling, which results in the phosphorylation and activation of HSF1 (32). These studies suggest that HSF1-dependent chaperoning of Hsp90 client proteins is dependent on growth factor (growth factor-PI3K-AKT) signaling.…”
Section: Ras-mapk and Mutant P53 Signaling In Tumorssupporting
confidence: 54%